Tailoring of rheological properties through hydrophobic interactions in silica-based liquid crystal gels - Sumana, S.; Chakrabortty, Pratyasha; Karumuthil, Subash Cherumannil; Prasad, S. Krishna; Prasad, Bhagavatula L. V. (ChemPhysChem, 2025)
Modification of the intrinsic hydrophilic character of the pristine silica nanoparticles (SiNP) decorated with silanol moieties into a hydrophobic state has been of substantial interest, owing to the amenability to gelation of desirable liquids. Many reports exist on composites of SiNP with liquid crystals (LCs), an epitome of anisotropic soft matter. The fumed SiNP, unlike its precipitated counterpart, has been the preferred variety. A family of colloidal gel systems is reported, consisting of precipitated SiNP in a nematic LC, formed by substituting some native silanols with methyl, butyl, or dodecane chains. Detailed steady state and oscillatory rheological measurements are performed, along with analyses using the soft glass and other viscoelastic models. The study demonstrates that the sophisticated modified fractional models, Kelvin-Voight and Maxwell, proposed for generalized viscoelastic behavior of soft materials, are quite successful in describing these nematic gels as well. The observed nontrivial relationship between the ligand length and the strength of the gel network is elucidated on the basis of a judicious combination of the van der Waals, hydrogen bonding, and hydrophobic interactions, leading to a detailed understanding of the viscoelastic behavior of the composites and the influence of SiNP surface chemistry.
Keywords: fractional viscoelastic models; Hydrophobic; nematic; rheological studies; silica nanoparticles